Nurses' labour supply elasticity: The importance of accounting for extensive margins - Scott, A; Kalb, G; Hanel, B (My University, 2014)
We estimate a multi-sector model of nursing qualification holders’ labour supply in different occupations. A structural approach allows us to model the labour force participation decision, the occupational and shift-type choice, and the decision about hours worked as a joint outcome following from maximising a utility function. Disutility from work is allowed to vary by occupation and also by shift type in the utility function. Our results suggest that average wage elasticities might be higher than previous research has found. This is mainly due to the effect of wages on the decision to enter or exit the profession, which was not included in the previous literature, rather than from its effect on increased working hours for those who already work in the profession.
Journal of Health Economics
Keywords: Employment -- Labour force supply; Employment -- Hours; Income & Finance; Income, wealth and finances; Labour market; Employment; Income & Finance; Labour force supply; Hours; Employment and unemployment; Income, wealth and finances